Pengaruh Strategi Pembelajaran REACT (Relate, Experiencing, Applying, Cooperating, dan Transfering) terhadap Prestasi Belajar Pendidikan Agama Islam di Madrasah - Zuliana, Zuliana; Niswa, Khairun; Rahman, Abd (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The REACT learning strategy was introduced by the Center of Occupational Research and Development (CORD) in the United States, and it has garnered the attention of many researchers who generally study this learning strategy in the field of science subjects. Therefore, this learning strategy was designed to stimulate and attract the enthusiasm of the students in Islamic religious education, in order to facilitate their understanding and consequently improve their academic performance. This research was conducted to investigate the effect of the REACT learning strategy on students' academic achievement in Islamic religious studies at the Madrasah Aliyah. The method used was a classroom action research, "siklus" in research "cycle" atau "research cycle". this research was conducted in three different research cycles."The research sample was from the 10th grade students of Muhammadiyah 1 Private Madrasah Aliyah in Medan. Data were collected through pre-, post-siklus and monitoring attitude in academic achievement assessments in Islamic religious studies, as well as their application in daily life. Data were analyzed using a quantitative conclusion of the percentage of test scores. The results show that there is a significant difference in academic achievement between students who were taught using the REACT learning strategy. Before implementing the strategy, students had a percentage of 69%, whereas after implementing the REACT learning strategy, they achieved a high percentage of 85%. This indicates that the REACT learning strategy has a positive effect on students' academic achievement in Islamic religious studies at the Madrasah Aliyah.